OPTIMALISASI CORPORATE SOSIAL RESPONSIBILITY BUMN UNTUK KAWASAN SUNGAI CIKAPUNDUNG BANDUNG - R Indriyati Kamil (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Today the application of CSR becomes increasingly important for the company. CSR has become a necessity for companies. The company's presence in the midst of society's dependence coined by people who are nearby. The relationship between the company and the community share the two sides of a coin that can not be separated. CSR also contributed positively to the relationship between the company and the community. Company as part of the community has a role in the community. Companies are not only economic benefits hunt alone, but also a concern for the environment and social welfare. State-Owned Enterprises (SOEs) have a strategic role and functions, as executor of public services, balancing large private forces, and helped small business development. SOE CSR role in the preservation of rivers such as helping the government to regenerate the river Cikapundung as a public space and also regarding the handling of flooding in the area around the River Cikapundung Bandung. To find the best solution in the structuring of public space in this Cikapundung riverbank, is very important to develop a policy of restoration of the river that can balance the interests of economic, social and environmental sustainability sustainable.